Controls Since the mid‐Pleistocene Transition on Sedimentation and Primary Productivity Downslope of Totten Glacier, East Antarctica. Issue 12 (22nd December 2020) - Holder, L.; Duffy, M.; Opdyke, B.; Leventer, A.; Post, A.; O'Brien, P.; Armand, L. K.
Abstract: The rapidly thinning Totten Glacier on the Sabrina Coast, East Antarctica, is the primary drainage outlet for ice within the Aurora Subglacial Basin, which could destabilize under the current atmospheric warming trend. There is growing need for direct geological evidence from the Sabrina Coast to frame late twentieth century Totten melting in the context of past warm climate analogs. Addressing this need, sediment archives were recovered from two sites on the Sabrina Coast slope and rise that record changes in terrigenous sedimentation and primary productivity in the region over glacial cycles since the mid‐Pleistocene transition (MPT). This research presents physical properties, grain size, diatom abundance and assemblages, and geochemical analysis from the two sites to determine how the processes that control sedimentation change between glacial and interglacial phases. The stratigraphic sequences in both cores record cyclic variations in physical properties and diatom abundances, which radiocarbon and biostratigraphic chronologies reveal as 100 Kyr glacial‐interglacial cyclicity. During glacials, terrigenous sediment deposition is enhanced by advanced grounded ice on the shelf, while primary productivity is restricted due to permanent summer sea ice extending past the continental slope. During interglacials, pelagic sedimentation suggests high surface productivity associated with contractions of regional sea ice cover. Comparison with post‐MPT slope records from Wilkes Land and the Amundsen Sea shows that this pattern is consistent in slope sediments around the margin. The higher‐amplitude variations in Antarctic ice volume and sea ice extent post‐MPT ensure that these signals are pervasive around the Antarctic margin. Plain Language Summary: To improve predictions of future Antarctic ice sheet behavior, knowledge of how Antarctica responded in the past, particularly when temperatures were similar to or higher than today, is required. Geological records recovered from ice proximal sediments can provide this information. The sediments record variations in physical, chemical, and biological properties and therefore act as indicators of paleoenvironmental change. Two sediment cores recovered from the Sabrina Coast continental slope and rise, East Antarctica, are used to study past changes in sediment deposition, as influenced by glacial and oceanographic processes. The two archives show clear variations in sediment composition and microfossil assemblage between glacial and interglacial conditions on 100 Kyr timescales over the last 350, 000 years, driven by the movement of the ice sheet across the continental shelf and the extent of sea ice cover. This research suggests that the drivers of sedimentation and the patterns revealed in slope sediments are consistent around the Antarctic margin due to the larger variations in climate since the mid‐Pleistocene transition. Key Points: Sedimentary archives from the Sabrina Coast continental slope document high‐amplitude glacial cycles since the mid‐Pleistocene transition Sedimentation and primary productivity are primarily controlled by sea ice extent and ice sheet position on the continental shelf These controls are amplified since the MPT and as a consequence influence sedimentation around the entire Antarctic Margin concurrently